Information Assurance Framework of Military Cloud - Baoping Guo; Jian1 Cheng; Weiping2 Liu (Dianxin kexue)
Due to the powerful capacity of information processing, on-demand and elastic service model, and enhanced security, cloud computing has become the future of military information system. At first, the conception and feature of cloud computing security was discussed. The current situation of research and application in military cloud security was analyzed. The objective of information assurance with military cloud was proposed on this foundation, then the architecture of information assurance with military cloud was structured, and the main modules of this architecture were analyzed in-depth. Lastly some key research opportunities were listed.